SHELTER CHARACTER REVIEW AS DISASTER MITIGATION FOR NATURAL DISASTER VICTIMS - Iryadini R.A, Nadhifia
Indonesia is one of the countries that has high potential against the threat of natural disasters. The National Disaster Management Agency (BNPB) noted that the number of natural disasters occurring during 2018-2019 has increased. Not only did they lose property and destroyed homes to the ground, but they also lost public facilities such as educational facilities, worship facilities, health facilities, and other public facilities. Consequently, this has a direct psychological impact on the victim, so that in a state of trauma temporary shelters are urgently needed by the victims after the disaster. Shelter is a program in disaster management during the emergency response period that is expected to be a shelter for disaster victims. Shelter plays an important role in reducing the risk of death and vulnerability and strengthening community resilience (IFRC, International Federation of Red Cross and Red Crescent Societies). Emergency shelters, temporary shelters, and permanent shelters are a form of gradual occupancy until they reach a livable shelter. The provision of shelter is expected to alleviate the suffering of disaster victims and protect victims from future disasters, but seeing conditions in the field, the needs and rights of disaster victims is still unfulfilled. This research aims to explain the type and character of shelters for victims of natural disasters ranging from the emergency period, transition, to permanent, therefore from these aspects will produce findings related to the character of disaster shelters in meeting the needs of their residents. In this study the authors used descriptive qualitative methods. Data collection is done with observation techniques, interviews and some secondary data in the form of literature, journals, guidebooks related to disasters, and factual news through electronic media, as well as YouTube. The process of data analysis method is done by comparatively each aspect studied and looking at the pattern of its relationship then linking the findings with disaster mitigation efforts. Analysis of the structure of space relationships is done by the Space Syntax analysis method. The results of this study produce a variety of shelter characters, among others: (1.) The types of disasters in Indonesia that cause many victims to lose their homes are types of severe disasters such as tsunamis, earthquakes, and landslides. (2.) Aspects of the type and shape of the building in the emergency shelter, while, until it still tends to be more permanent the building is more complex. The organization of forms applied to disaster shelters is linear form and clustered form with tread house building type and stage house; (3.) The size of the shelter is more 6 permanent, the larger the size; (3.) Aspect of space programs is the more permanent, the more the space program is formed. Emergency shelters do not have space programs, temporary shelters have space programs that are private spaces and public spaces, while permanent shelters are private spaces, public spaces, and service rooms; (4.) The accessibility of space in the shelter also forms a process where the more permanent the building, the more relationships between the spaces. The most space relationships are public spaces that tend to be in the front area, while the privacy space tends to be located in the back area so that the relationship is less; (5.) Building materials used vary, emergency shelters use more tent materials such as tarpaulins, TNI standard soft D300s, and polyesters, while temporary shelter buildings tend to use environmentally friendly materials such as bamboo, and wood, then shelters still tend to use local materials or building materials such as light concrete wood and light steel; (6.) Construction system in makeshift tent is portable and easy to move, the construction system used only in the form of tent frame and rope, while the average temporary shelter uses earthquake friendly residential system and uses knockdown system so that it can be easily disassembled due to its temporary nature, then shelter still also implements earthquake friendly housing system and has 3 types of structures namely concrete structure, wood and light steel.